2011
DOI: 10.4048/jbc.2011.14.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Scalpel, Electrocautery and Ultrasonic Dissector Effects: The Impact on Wound Complications and Pro-Inflammatory Cytokine Levels in Wound Fluid from Mastectomy Patients

Abstract: PurposeIntroducing the relationship between the surgical instruments used in modified radical mastectomy and wound complications is important for preventing and decreasing complications. This prospective randomized trial was designed to assess the impact of scalpel, electrocautery, and ultrasonic dissector usage on wound complications and tissue damage.MethodsEighty-two consecutive patients operated with mastectomy were studied. The postoperative time period needed for hemovac drainage, the amount and duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 20 publications
0
83
2
5
Order By: Relevance
“…There are few other published studies comparing sharp dissection with electrocautery dissection and these tend to be in breast patients. Yilmaz et al 11 looked at seroma formation post mastectomy and suggest electrocautery use may lead to an increase in seroma formation although numbers are small and seroma rates high in both knife and electrocautery group (37% and 53.8% respectively). Others have found that in thyroidectomy patients use of electrocautery or scalpel for flap dissection does not significantly affect seroma formation 12 whereas Porter et al 13 suggested electrocautery leads to an increase in seroma formation post mastectomy (38% v 13% p Z 0.01) although the results were only significant at the 90% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…There are few other published studies comparing sharp dissection with electrocautery dissection and these tend to be in breast patients. Yilmaz et al 11 looked at seroma formation post mastectomy and suggest electrocautery use may lead to an increase in seroma formation although numbers are small and seroma rates high in both knife and electrocautery group (37% and 53.8% respectively). Others have found that in thyroidectomy patients use of electrocautery or scalpel for flap dissection does not significantly affect seroma formation 12 whereas Porter et al 13 suggested electrocautery leads to an increase in seroma formation post mastectomy (38% v 13% p Z 0.01) although the results were only significant at the 90% confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Here, levels of other pro-inflammatory cytokines such as monocyte chemotactic protein-1 (MCP-1) were elevated, as were levels of antiinflammatory cytokines TGF-1, TGF-2, and TGF-3 but not IL-10. Yilmaz et al compared the use of a scalpel, electrocautery and ultrasonic dissection during mastectomy [20]. Interesting, electrocautery induced significantly higher levels of cytokines than scalpel and ultrasonic dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of such oc curences varies widely according to the type of surgical treat ment and the operative techniques used, ranging from less than 10% to more than 50% [5]. Electrocautery is one named cause of seroma formation in the literature [6]. The seroma formation is the next step coming after prolonged drainage duration and increased drainage amount, however we couldn't establish the statistical difference between the groups because of the small sample size.…”
Section: Discussionmentioning
confidence: 91%